Implementasi Metode Collaborative Planning Forecasting and Replenishment untuk Minimasi Bullwhip Effect pada Supply Chain (Study Kasus: PT. XYZ ) - M Hafizh Hasan Al Marufi; Jaka Purnama; Made Kastiawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is a car mat manufacturing company in Surabaya facing challenges due to sharp, fluctuating client demands and uncertainties in material procurement. The bullwhip effect occurring within the company poses a high risk of raw material overstock mat, as well as stockout risks that can cause production downtime. This study aims to measure the existing bullwhip effect value, analyze material handling, and compare the effectiveness of quantitative forecasting methods under the Collaborative Planning, Forecasting, and Replenishment (CPFR) framework. Initial identification confirmed demand amplification, with bullwhip effect values of 1.349 in 2024 and 1.183 in 2025. Based on comparative accuracy testing for projecting the next 12 months' demand, the ARIMA (2,0,0) model was selected as the optimal method as it produced the minimum error value, with a Root Mean Squared Error (RMSE) of 2118.37 and a Mean Absolute Percentage Error (MAPE) of 7.93%. Utilizing this selected model, inventory control planning can be optimized, establishing the safety stock after forecasting at 3,978 units with a constant 1-month lead time.